Distribución geográfica de la especie Cedrelinga cateniformis Ducke en la región Loreto-2020 - Machoa Flores, Gino Di Angelo (2021)
Currently, less than 20 species of the Peruvian Amazon Forest with economic value are commercialized at the national and international market; many of them in the Loreto region are characterized by presenting the highest volumes of commercial timber mobilized in Peru. However, attributes such as the geographical distribution of each species are still few known. Among them, Cedrelinga cateniformis Ducke, is a species with different technological characteristics that makes it attractive to national and international markets. The objective of the research was to determine the geographic distribution of the Cedrelinga cateniformis Ducke species in the Loreto region. The data was modeled with MaxEnt, an algorithm used in species distribution models, using data on the presence of the species, with diameter at breast height (DBH) ? 61 cm, collected from forest inventories supervised by OSINFOR between 2009 and 2019 in the Loreto region) and environmental variables (bioclimatic, topographic and edaphic) with a resolution of 1 km2. The results indicate that bioclimatic variables (temperature and precipitation seasonality) and edaphic variables (clay content) determine the geographical distribution of the Cedrelinga cateniformis Ducke species in the Loreto region, explaining more than 70% of its geographical distribution. The model yielded acceptable values (AUC = 0.794) of habitat conditions where the species can develop based on the variables analyzed. Establishing the variables that determine the presence of the species contributes to reducing the scarce knowledge about the characteristics of habitat and distribution.